Prediction for the surface settlement of double-track subway tunnels for shallow buried loess based on peck formula - Wang, Shuangyuan; Song, Zhanping; Tian, Xiaoxu; Sun, Yinhao; Zhang, Yuwei (Frontiers in Earth Science, 2023)
In the process of constructing double-track subway tunnels in shallow buried loess area, the interaction of double-track tunnels is significantly influenced by the net distance and the cross-section size, which is challenging to control the surface settlement. Therefore, the surface settlement prediction is essential while constructing double-track subway tunnels in shallow buried loess area. Firstly, the paper analyzed the surface settlement mechanism regarding shallow double-track subway tunnels, with the decrease of the net distance, the surface settlement superimposed curve was double V shape -W shape -single V shape. When the superimposed curve is double V shape and W shape, the Peck formula was used to calculate the surface settlement curve of the single-track tunnel, then superimposed to obtain the final surface settlement curve. When the superimposed surface settlement curve was V shape, based on the Peck formula, the formula for predicting the surface settlement suitable for symmetry and asymmetry was established. the net distance ratio and the area ratio were defined, and considering the tunnel's interaction, the value and position of the maximum were corrected. Then numerical tests were carried out 16 times with different net distance ratios and area ratios, to determine the parameters of increments and position offsets of the maximum regarding the net distance ratio and the area ratio. Finally, two engineering were conducted for verifying the rationality and applicability exhibited by the prediction formula. The prediction formula served for predicting the surface settlement of double-track subway tunnels in shallow buried loess area. which can reduce construction risks and assure the safety of buildings above the ground.